Soil nitrate drives fine root decomposition under nitrogen addition in a subtropical forest - Chen, Guantao; Chen, Yuqin; Yao, Xingzhu (Frontiers in Forests and Global Change, 2025)
Fine root decomposition is a key process influencing the element cycling of forest ecosystems and is sensitive to increasing atmospheric nitrogen (N) deposition. However, the specific relationship between soil chemical characteristics and the nutrient release patterns of fine root decomposition under increasing N deposition is not fully understood. We conducted a decomposition experiment with three N addition levels using lower order (order 1–3) and higher order (order 4–5) of Castanopsis platyacantha fine root and observed its decomposition rates and nutrient dynamics from March 2016 to April 2018 in a subtropical forest of China. Soil pH, carbon fractions, and N fractions were measured and served as explanatory variables to explore the relationship with root decomposition rates through stepwise linear regression. After 2 years of decomposition, high N addition had a larger mass remaining than the control treatment for the lower-order root. Soil nitrate greatly explained the root decomposition rates among N treatments (R2 = 0.712 for lower-order roots and R2 = 0.520 for higher-order roots). Nitrogen addition did not affect the remaining root N, P, K, Ca, Mg, and Mn. The remaining ratio of C/P and C/Mn in lower-order roots and C/Mn in higher-order roots was significantly increased in high N addition. Our results indicated that among different N treatments, soil nitrate content significantly affected rates of fine root decomposition in subtropical forests in China. However, N addition did not significantly affect the amount of nutrients released during root decomposition except for significantly changing the release rate of P in lower-order roots and Mn in both lower- and higher-order roots. In the future, the impact of N deposition on Mn cycling and its further effect on C storage in forests deserves attention.